2018
DOI: 10.1007/s40430-018-1396-x
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of a variable stroke and compression ratio mechanism of an internal combustion engine

Abstract: The development of automotive propulsion has been guided in recent years by policies for the reduction of pollutant emissions. To comply with the imposed regulations, engine adaptability is one of the most effective strategies for meeting efficiency requirements in the case of the diverse operational conditions found in urban traffic. A variable stroke and compression ratio engine is the solution to this requirement. In addition to its advantages, its design inevitably increases the engine's complexity. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The simulated engine consists of the mechanism described in Rufino and Ferreira, 13 that is, a naturally aspirated spark-ignition engine with port-fuel injection. Properties of anhydrous ethanol are given in Table 2.…”
Section: Characteristics Of the Simulated Enginementioning
confidence: 99%
See 1 more Smart Citation
“…The simulated engine consists of the mechanism described in Rufino and Ferreira, 13 that is, a naturally aspirated spark-ignition engine with port-fuel injection. Properties of anhydrous ethanol are given in Table 2.…”
Section: Characteristics Of the Simulated Enginementioning
confidence: 99%
“…[10][11][12] Therefore, the authors developed a new technology involving the addition of a lever between the connecting rod and piston; this allows the piston kinematics to be controlled by the position of the lever's pivot. 13 By controlling piston kinematics, the position of top dead centre (TDC) can be regulated, thus controlling both the compression ratio and the displacement. A schematic of the specific mechanism studied herein is presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Khader 12 proposed the design nomograms for directly designing the crank-rocker mechanism links’ ratios with a definite determined transmission angle limit. Rufino and Ferreira 13 described a variable stroke mechanism and presented a kinematic model to determine the requirements for synthesis of the mechanism. El-Shakeryet al 14 suggested both analytical and graphical methodologies to optimally determine links’ lengths of crank-rocker four-bar linkage to obtain a targeted design with definite transmission angle.…”
Section: Introductionmentioning
confidence: 99%
“…Khader 15 proposed the design nomograms for directly designing the crank-rocker mechanism links’ ratios with a definite synthesized transmission angle range. Rufino and Ferreira 16 described a variable stroke mechanism and presented a kinematic model to determine the requirements for synthesis of the mechanism. El-Shakery et al 17 suggested both analytical and graphical methodologies to optimally synthesize links’ lengths of crank-rocker four-bar mechanism to achieve a targeted design with definite transmission angle.…”
Section: Introductionmentioning
confidence: 99%